SMALL AMBITUS – NEW STYLE CHRISTMAS CAROLS FROM THE TRANSYLVANIAN PLAIN - Zoltán GERGELY (Studia Universitatis Babeş-Bolyai. Musica, 2018)
Folk music literature includes into the group called small ambitus new style all those melodies, which present a domination of tonal characteristics. Besides the two most well known and most popular examples of the Christmas carols repertoire from the Transylvanian Plain, there are also two other melodies, which were integrated into the local Christmas repertoire only in one single settlement.